Merging Markets - Arnold, Tom; Hersch, Philip; Mulherin, J. Harold; Netter, Jeffry (Journal of Finance, 1999)
We study the causes and effects of the competition for order flow by U.S. regional stock exchanges. We trace the origins of competition for order flow to a change in the role of regional exchanges from being venues for listing local securities to being more direct competitors for the order flow of NYSE listings. We study the way regionals competed for order flow, concentrating on a series of stock‐exchange mergers that occurred in the midst of this transition of the regional exchanges. The merging exchanges attracted market share and experienced narrower bid‐ask spreads.